Docosahexaenoic acid-loaded chitosan/alginate membrane reduces biofilm formation by P. aeruginosa and promotes MSC-mediated burn wound healing. (March 2023) - Ghaneialvar, Hori; Kayumov, Airat; Aboualigalehdari, Elham; Pakzad, Iraj; Tanideh, Nader; Abbasi, Naser; Haddadi, Mohammad Hossein
Aims: Chitosan, like docosahexaenoic acid (DHA) and mesenchymal stem cells (MSCs), is used in medicine as a wound healing accelerator. Thus, in this study, chitosan-alginate (CA) membranes containing DHA and MSCs were produced, and their antibacterial and antibiofilm activities against burn infections caused by Pseudomonas aeruginosa were investigated. Methods: Physicochemical properties were assessed by SEM, Fourier transform infrared (FTIR), and X-ray diffraction (XRD). Porosity, cytocompatibility, and antibacterial and antibiofilm activities were evaluated both in vitro and in vivo. The viability and apoptosis of MSCs were studied using flow cytometry. Wound healing effects were analyzed based on histopathological features, the wound contraction rate (WCR) ratio, and bacterial clearance. Results: The CA membranes showed antibiofilm activity both in vivo and in vitro, accompanied by reduced lasI and rhlI expressions and pyocyanin production. The membranes were highly porous and biocompatible and showed favorable physicochemical properties. Docosahexaenoic acid incorporation to CA membranes improved their antibacterial and antibiofilm activities, as well as MSCs' viability by reducing crystallinity and increasing porosity ( p = .008 ). Treatment with CA-DHA-MSC accelerated burn wound healing (with complete healing being observed after 14 days, WCR = 85%) and augmented antibacterial and antibiofilm activities in vivo compared to CA-DHA and CA-MSC. The CA-DHA-MSC group delivered a significantly higher WCR and lower inflammation than the CA-MSC group ( p = .0001). Conclusion: In combination with DHA-loaded CA membranes, MSCs reduced the healing time of burn wounds, offering a viable option for designing effective wound dressings. Graphical Abstract